Sosialisasi Penyusunan Modul Ajar Bagi Guru Madrasah Ibtidaiyah Rifaiyah Limpung - Khusnaini, Mukh; Suryaningrum, Sumarah; Simal, Rufiati; Mautang, Hizkia G.; Kahar, Siti Rahmawati (Abdimas Indonesian Journal, 2025)
This community service activity was carried out as an effort to improve the professional competence of Madrasah Ibtidaiyah (MI) teachers in developing teaching modules that are in line with the independent curriculum and student needs. The background to this activity stems from the finding that most MI teachers still experience difficulties in understanding the structure and components of teaching modules, especially in designing integrated learning objectives, learning outcomes, and assessments. The focus of this activity is to provide socialization and technical assistance in developing teaching modules based on student characteristics and the local context of the madrasah. The activity implementation method uses a participatory approach through the stages of preparation, implementation of socialization, assistance in the practice of developing teaching modules, and evaluation of the results of the activity. Participants consisted of 23 teachers from MI Rifaiyah Limpung, Limpung District, Batang Regency. The results of the activity showed an increase in teachers' understanding and skills in developing teaching modules that are more systematic and relevant to learning needs. In addition, participants demonstrated high enthusiasm in adapting the format and principles of developing teaching modules in accordance with the curriculum guidelines. Based on the evaluation results, 85% of participants were able to produce teaching module designs that met the criteria for completeness and appropriateness of content. Thus, this socialization activity has proven effective in strengthening the capacity of MI Rifaiyah Limpung teachers in designing innovative and contextual teaching tools, as well as supporting the improvement of the quality of the learning process at the madrasah.